Generation of αGal-enhanced bifunctional tumor vaccine - Jian He; Yu Huo; Zhikun Zhang; Yiqun Luo; Xiuli Liu; Qiaoying Chen; Pan Wu; Wei Shi; Tao Wu; Chao Tang; Huixue Wang; Lan Li; et al. (Elsevier, 2022)
Hepatocellular carcinoma (HCC) is a common malignant tumor with poor prognosis and high mortality. In this study, we demonstrated a novel vaccine targeting HCC and tumor neovascular endothelial cells by fusing recombinant MHCC97H cells expressing porcine α-1,3-galactose epitopes (αGal) and endorphin extracellular domains (END) with dendritic cells (DCs) from healthy volunteers. END+/Gal+-MHCC97H/DC fusion cells induced cytotoxic T lymphocytes (CTLs) and secretion of interferon-gamma (IFN-γ). CTLs targeted cells expressing αGal and END and tumor angiogenesis. The fused cell vaccine can effectively inhibit tumor growth and prolong the survival time of human hepatoma mice, indicating the high clinical potential of this new cell based vaccine.